Production model under Lean manufacturing and change awareness approaches to reduce order delays at small and medium-sized enterprises from the clothing sector in Peru - León-Guizado, Sheyene (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.